2022
DOI: 10.1002/jcop.22900
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the role of resilience and life satisfaction as mediators of the impact of COVID‐19 worries on mental health

Abstract: The aim of this study was to test whether resilience and life satisfaction (two traditional protective factors) mediate between COVID-19 related worries and the development of symptoms of depression, anxiety, and stress in adolescents and young adults. Participants involved 392 adolescents and young adults (70.20% female) aged between 12 and 25 years (M = 17.05 years, SD = 3.08). Participants completed the COVID-19 related worries scale, the CD-RISC to analyse resilience, the Satisfaction with Life Scale, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
5
9
0
Order By: Relevance
“…It is plausible that heightened levels of perceived stress impact life satisfaction, which in turn negatively impacts mental health. This finding supports research findings by Tamarit and colleagues pertaining to the mediating role of life satisfaction in the relationship between COVID-19-related worries and depression and COVID-19-related worries and anxiety [ 51 ]. The finding can also be explained through cognitive appraisal theory [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is plausible that heightened levels of perceived stress impact life satisfaction, which in turn negatively impacts mental health. This finding supports research findings by Tamarit and colleagues pertaining to the mediating role of life satisfaction in the relationship between COVID-19-related worries and depression and COVID-19-related worries and anxiety [ 51 ]. The finding can also be explained through cognitive appraisal theory [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Besides a direct relationship between life satisfaction and depression, studies also showed that life satisfaction mediated the association between COVID-19 stresses and depression. For example, Tamarit et al (2022) revealed that resilience and life satisfaction mediated the association between pandemic-related worries and negative emotional symptoms (depression, anxiety, and stress). Coello et al (2022) also showed that life satisfaction had a mediating role in the relationship between pandemic-related worries and depression, anxiety, and stress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, positive mental health indicators such as life satisfaction was found to be positively correlated with resilience (Aboalshamat et al, 2018 ; Zheng et al, 2020 ), subjective well – being (Liu et al, 2014 ). Similar to resilience, life satisfaction serves as an individual barrier against the danger of depression (Tamarit et al, 2022 ). The above analyses suggest that high life satisfaction can increase resilience and reduce the risk of depression.…”
Section: Introductionmentioning
confidence: 99%